Observables physics general formalism - Iyer, Rajan (Physics & Astronomy International Journal, 2022)
Observables form the most important real physics proof processes that will make normal science. Since mathematics have integral part in quantifying physical phenomena, theory involves modeling hypothetical logic borne within observations. A proper theory will need to show pulling out observables from parameters using abstractions. These processes that have gotten derived elsewhere are reviewed here in a gist manner that author has been able to configure as a fundamentally grand unifying realistic physics without assumptive inconsistencies. Review here also shows corrections of errata in earlier publications to help applications to wider areas of not only physical sciences but also mathematical computing information technology algorithms’ developments. Iyer-Markoulakis formalism to gage micro to macro by applying Coulomb-Hilbert gage from mechanics of gradient vortex fields to electromagnetic fields and then to gravitational aspects have been explained. Quantitative derivation of a general potential wave quantum density commutator matrix physics, with subsequent gauge equivalent expressions have been advanced. Mathematical modeling has been briefed on theorizing point dynamics Helmholtz decomposition fields’ quantum Hamiltonian matrix evolving with time. Partial differential equations that have gotten derived from these characteristic matrices for zero-point as well as microblackhole aspects of a point in sense-time-space dimensions have highlighted addressing real world complexity manifested by these pure logical equations. Gaging with algorithmically elaboratively extended analysis with observables provide fitting completions to the partial differential equations (P.D.E.) of energy and quantum field metrix within Iyer-Markoulakis-Hodge-O’Neill-Malaver-Zhang-Taylor formalisms that provide best hope towards grand unification of the four super forces that physics portrays to natural workings of the universe. Retrofitting Iyer Markoulakis gradient vortex gage fields eigen matrix formalism to Wenzhong Hodge scalar frictional vacuum theory of hod-Plenum, dissipative discontinuity of modeling gage physics, giving an Integral Model Astro Quantum PHYSICS has shown to be achievable. Matrix general form algorithm equation, having gage functional, signal/noise ratio, gage fields, wavefunction inner outer products, quantum density matrix as a function of gage time configured successfully. Application to observables practically for analysis has been exemplified to mesoscopic population pattern with gage fields of pressure and temperature.